2015
DOI: 10.1155/2015/179483
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Tuberculoma in Pregnancy

Abstract: We report a case of a Somali refugee who presented in the second trimester of her first pregnancy with a four-week history of gradual right-sided sensomotoric hemisyndrome including facial palsy and left-sided paresis of the oculomotorius nerve causing drooping of the left eyelid and double vision. Cranial magnetic resonance imaging revealed a solitary brainstem lesion. Upon detection of hilar lymphadenopathy on chest X-ray (CXR), the diagnosis of disseminated tuberculosis with involvement of the central nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Malnutrition, immunosuppressed status, and other comorbidities affect the disease course, which leads to a flare [6]. Besides that, suppression of Th1 in pregnancy leads to increased infection susceptibility and TB reactivation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition, immunosuppressed status, and other comorbidities affect the disease course, which leads to a flare [6]. Besides that, suppression of Th1 in pregnancy leads to increased infection susceptibility and TB reactivation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that the immunosuppression related to pregnancy could lead to infectious processes similar to that occurs in immunocompromised hosts ( 15 , 16 ). The T-helper 1 (Th1) proinflammatory response is suppressed during pregnancy, increasing susceptibility to new infections and reactivation of TB, but after delivery, Th1 suppression reverses, exacerbating symptoms and making women twice as likely to develop TB in the early postpartum period compared to women who had not been pregnant ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…They behave like space-occupying lesions and present with signs of raised intracranial pressure, localized neurological deficits, seizures, and even behavioral problems [ 13 ]. Seizures are one of the most common symptoms occurring in up to 85% of cases along with symptoms related to elevated intracranial pressure such as headache, papilledema, and lethargy [ 33 ]. Our patient presented signs and symptoms of meningoencephalitis and space-occupying lesions: headache, vomiting, fever, altered mental status to soporous state, right hemiparesis, and generalized seizures.…”
Section: Discussionmentioning
confidence: 99%